EFEKTIVITAS PELAKSANAAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 1 TAHUN 2020 TENTANG KEBIJAKAN KEUANGAN NEGARA DAN STABILITAS SISTEM KEUANGAN UNTUK PENANGANAN PANDEMI COVID-19 - Daud, Irham; Tumuhulawa, Arifin; W. Amu, Robby (At-Tanwir Law Review, 2024)
This study aims to examine and analyze the Financial Policy Implementation Mechanism in the Formulation of the 2020 Regional Budget Draft in the context of Budget Recofusing Related to Handling the COVID-19 Pandemic in Boalemo Regency. And analyze the Effectiveness of the Implementation of Government Regulation in Lieu of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the COVID-19 Pandemic in Boalemo Regency. is Empirical, which is research that will be carried out by researchers by going directly to the field, to find out directly the answers from informants / respondents. The results showed that the Financial Policy Implementation Mechanism in the Formulation of the 2020 Regional Budget Draft in the Framework of Budget Recofusing Related to Handling the COVID-19 Pandemic in Boalemo Regency was based on Presidential Instruction Number 4 of 2020 on March 20 and the Implementation of Government Regulation in Lieu of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the Pandemic COVID-19 in Boalemo Regency has not been effective by conducting a more in-depth analysis and considering these various factors.